2014
DOI: 10.1111/anae.12830
|View full text |Cite
|
Sign up to set email alerts
|

A performance comparison of the paediatric i‐gel with other supraglottic airway devices

Abstract: SummaryWe performed a review of published literature comparing the i‐gel™ with other supraglottic airway devices in children. Sixty‐two articles were identified following a literature search; we included data from 14 randomised controlled trials and eight observational studies that compared i‐gel sizes 1–2.5 with other commonly used, equivalently‐sized, devices. The primary outcome in most studies was oropharyngeal leak pressure. In the 14 randomised trials the i‐gel performed the same as the comparator device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 87%
“…The initial airway leak pressures in this study for the AuraGain are similar to previous studies with the LMA Supreme [1,5,6,12], but slightly lower than the reported airway leak pressures of the LMA ProSeal [2,13] and i-gel [14][15][16] in children. The slight increase in airway leak pressures at 10 min in this study is suggestive that the airway sealing characteristics remain relatively stable during the initial phase of anaesthetic maintenance.…”
Section: Discussionsupporting
confidence: 87%
“…, Montblanc et al. , Smith & Bailey , and Baidya et al. , may help distill what clinical evidence we do have and identify outcomes for which there is still insufficient evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of evidence‐based medicine, introduction of a new device into clinical practice must be justified first with scientific reasoning. In this and recent issues of Anaesthesia , such evidence is provided by way of three meta‐analyses on the i‐gel ® and one on the Ambu ® AuraOnce ™ .…”
Section: How Can We Choose the ‘Right’ Device?mentioning
confidence: 99%
“…The i‐gel may have a slight advantage in practicality since institutions may be less inclined to use reusable devices, such as the ProSeal. Furthermore, the i‐gel's mask material of thermoplastic elastomer that adapts to the shape of the patient's pharynx creates a superior seal compared to many other devices, including the Laryngeal Mask Airway Classic and Laryngeal Mask Airway Unique, Supreme, and ProSeal . The i‐gel's additional advantage is that its mask does not involve a cuff that can be inflated.…”
Section: The “Best” Of What We Havementioning
confidence: 99%